Trimming of nails in healthy dogs does not change gait parameters when comparing pre- and post-nail trim - Häusler, Kirsten; Söhnel, Katja (Frontiers in Veterinary Science, 2026)
Claw length in dogs is widely assumed to influence gait, with the belief that excessively long claws may alter locomotion patterns and lead to musculoskeletal issues. Still today, this hypothesis lacks objective data. This is the first study to investigate the potential impact of claw length on canine gait using validated pressure-sensing treadmill analysis in a small cohort of clinically healthy dogs, both before and after claw trimming. Contrary to common assumptions, no significant differences in gait parameters, such as stride length, stance phase duration, or vertical ground reaction forces, were observed before and after claw trimming. Length of the front paws was 2 mm longer before nail trimming (p = 0.022), and the medio-lateral center of pressure movement was slightly decreased by 1% of paw width before nail trimming (p = 0.018). The observed absence of differences in temporospatial and kinetic parameters suggests that, although local paw-level mechanics such as medio-lateral COP or paw length may be affected by claw length, these alterations do not translate into functional changes in global gait parameters. This supports the conclusion that, in clinically sound dogs, longer claws do not impair overall locomotor function. These findings suggest that long claws may not be the cause of altered gait, but rather a consequence of decreased natural abrasion due to abnormal or inefficient gait. This insight shifts the focus from claw length as a primary problem to underlying biomechanical issues that may hinder normal claw abrasion. Further studies are needed to explore the relationship between gait quality and claw health.